A NSGA-II Based Peak Load Shifting Optimization Method for Customers with Distributed Generators Considering Time-of-use Price - Zhou, Hao; Ding, Min; Hu, Bo; Wang, Qingyi; Tan, Zhili; Li, Danyun (Chinese Control Conference, 2018)
With the extensive use of distributed generation, the traditional demand response analysis cannot meet the current requirements. This paper proposes a NSGA-II based peak load shifting optimization method for customers with distributed generators considering time-of-use price. Firstly, a fuzzy classification method divides the daily power into three time segments, peak hours, flat hours and valley hours. Secondly, on the basis of the time-of-use price, a peak load shifting optimization model is built with constraints and the objectives of minimizing the peak load, maximizing the valley load, and minimizing the peak-valley difference. Then, a NSGA-II based optimization method solves the optimal model and obtains the optimal electricity prices of different time segments to shift the peak load and the valley load. Finally, the simulation results shows the effectiveness of the proposed method.